Influence of species composition and cultivation condition on peri-implant biofilm dysbiosis in vitro - Heine, Nils; Bittroff, Kristina; Szafrański, Szymon P.; Duitscher, Maya; Behrens, Wiebke; Vollmer, Clarissa; Mikolai, Carina; Kommerein, Nadine; Debener, Nicolas; Frings, Katharina; Heisterkamp, Alexander; Scheper, Thomas; et al. (Frontiers in Oral Health, 2025)
IntroductionChanges in bacterial species composition within oral biofilms, known as biofilm dysbiosis, are associated with the development of severe oral diseases. To better understand this process and help establish early detection systems, models are needed which replicate oral biofilm dysbiosis in vitro – ideally by also mimicking natural salivary flow conditions.MethodsFor this purpose, the present study cultivated two different combinations of oral commensal and pathogenic strains – Streptococcus oralis, Actinomyces naeslundii, Veillonella dispar/parvula, Fusobacterium nucleatum and Porphyromonas gingivalis – comparatively within an established flow chamber model on the implant material titanium, and statically in 6-well plates for 21 days. Biofilm morphology, species distribution, and bacterial metabolism were analyzed by fluorescence microscopy, molecular biological methods, and metabolic interaction prediction.ResultsBiofilm growth and composition were strongly influenced by bacterial species selection, and to a more minor extent, by cultivation conditions. Within the model containing V. dispar and a laboratory P. gingivalis strain, a diversification of commensal species was observed over time along with a significantly reduced pH-value. In contrast, the model containing V. parvula and the clinical isolate P. gingivalis W83, a dysbiotic shift with increased pathogen levels, pH-value, and virulence factors was achieved.ConclusionWithin the present study, different in vitro oral multispecies biofilm models were successfully developed. Depending on bacterial species selection, these models were able to depict the infection-associated dysbiotic shift in species composition under flow conditions solely by intrinsic interactions and without the use of external stimuli.